2014
DOI: 10.2151/jmsj.2014-105
|View full text |Cite
|
Sign up to set email alerts
|

An Intensification Process of a Winter Broad Cloud Band on a Flank of the Mountain Region along the Japan-Sea Coast

Abstract: During a cold-air outbreak between 25 and 27 January 2009, a broad cloud band formed along the coastal region from San-in to Hokuriku on the Sea of Japan side of the Japanese Islands. Along the mountain flank, precipitation in the cloud band was intensified. Intensification processes of the broad cloud band and microphysical characteristics of the intensified precipitation region were examined. During the lifetime of the cloud band, two low-pressure systems successively developed in the central Sea of Japan. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Cloud bands form and intensify offshore and/or onshore along the western coasts of the Japanese islands under the influence of coastal topography and land breezes. These cloud bands, which bring heavy snowfall to the coastal and plain areas, have been investigated primarily by using Doppler radar (Sakakibara et al 1988b;Ishihara et al 1989;Fujiyoshi et al 1992;Yoshimoto et al 2000;Ohigashi and Tsuboki 2005;Ohigashi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud bands form and intensify offshore and/or onshore along the western coasts of the Japanese islands under the influence of coastal topography and land breezes. These cloud bands, which bring heavy snowfall to the coastal and plain areas, have been investigated primarily by using Doppler radar (Sakakibara et al 1988b;Ishihara et al 1989;Fujiyoshi et al 1992;Yoshimoto et al 2000;Ohigashi and Tsuboki 2005;Ohigashi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed the intensification of snow clouds near the coast and their dissipation after a landfall. Snow clouds are intensified near the coast due to various factors; the variation in vertical wind shear (Takeda et al 1982), locally produced convergence by orographically deflected winds (Yoshihara et al 2004;Ohigashi et al 2014), and interaction with land-breeze (Ishihara et al 1989;Tsuboki et al 1989;Ohigashi and Tsuboki 2005). It is also known that, due to the larger surface roughness and resultant larger cross-isobaric wind component over land, mesoscale convergence zone can be generated along the coast downwind of the prevailing wind (Markowski and Richardson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During a sea-effect event in the Hokuriku region, Kusunoki et al (2003) found that higherĤ periods tended to have shallow clouds confined to the windward slopes, with the precipitation deepening and moving over the barrier asĤ decreased. In another event, flow blocking maintained a persistent nearshore sea-effect band (Ohigashi et al 2014). In addition to allowing flow to surmount a barrier, FIG.…”
Section: Introductionmentioning
confidence: 94%
“…L-mode bands are oriented quasi-parallel to the flow and occur during periods of weak directional shear within the PBL, whereas T-mode bands are oriented quasi normal to the flow and occur during periods of strong directional shear (e.g., Asai 1972;Miura 1986;Eito et al 2010;Yamada et al 2010). Broad, mesoscale snowbands can also be produced by the Japan Sea polar airmass convergence zone (JPCZ), which forms frequently over the western SOJ downstream of the base of the Korean Peninsula (e.g., Ohigashi and Tsuboki 2007;Eito et al 2010;West et al 2019). The JPCZ can produce intense precipitation where it intersects the coast of Honshu, most frequently between ;1338 and ;1398E, including the Hokuriku region (Eito et al 2010).…”
Section: Introductionmentioning
confidence: 99%